Analysis of Customer Experience and Electronic Service Quality on Purchasing Decisions of Products on Tokopedia (A Case Study of Residents in Medan Kota District) - Muhammad Fauzan Akbar; Erwansyah Erwansyah; Megasari Gusandra Saragih (Journal of Management, Economic, and Accounting, 2026)
This study aims to determine the influence of customer experience and e-service quality on purchasing decisions for products on Tokopedia. The object of this research is the community of Medan Kota District. The population and sample of this study consisted of 96 respondents. Data processing was carried out using SPSS version 24. The data were tested using classical assumption tests and multiple linear regression analysis. The results show that the t-test for the pengalaman pelanggan variable (X1) obtained a t-value of 2.099 > t-table 1.985 with a significance value of 0.039 < 0.05, which means that the customer experience variable has a positive and significant partial effect on purchasing decisions. The t-test for the e-service quality variable (X2) obtained a t-value of 2.173 > t-table 1.985 with a significance value of 0.032 < 0.05, indicating that the e-service quality variable also has a positive and significant partial effect on purchasing decisions. The F-test results show that the F-value is 17.839 > F-table 2.704 with a significance value of 0.000 < 0.05. The R² value of 0.262 or 26.2% indicates that the independent variables — customer experience (X1) and and e-service quality (X2) — are able to explain 26.2% of the variation in the purchasing decision variable (Y).